STRATEGIC INTELLIGENCE ANALYSIS OF RELIGION-BASED HATE SPEECH IN SOCIAL MEDIA: A CASE STUDY OF THE DIRECTORATE INTELLIGENCE AND SECURITY AT POLDA METRO JAYA - Prakoso, Gilang Reno; Runturambi, Arthur Josias Simon (UI Scholars Hub, 2021)
The development of communication technology continues to advance rapidly. Social media is able to present individual voices that have never been heard through mainstream media coverage before. In Indonesia, the changes in the world have become increasingly clear when the era of communication has flooded the lives of religious communities. Religious discourse in Indonesia in recent years has been colored by accusations of religious intolerance in the form of hate speech through social media. The prohibition on the construction of houses of worship, prohibition of book discussions, attacks on certain groups, heresy from certain religious groups, threatening expressions of hatred, and so on are a series of acts of religious intolerance so that the potential for social conflict appears clearly. The Police Intelligence and Security as an institution that has the obligation to carry out early detection of threats must play an active role in making prevention and anticipation efforts. This research examines the Strategic Intelligence Analysis of Religious-Based Hate Speech on Social Media by the Directorate of Intelligence and Security at Polda Metro Jaya.